Ressonância de Kondo dependente da temperatura - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
In this work we have calculated the magnetic susceptibility χ, the specific heat C and a electrical resistivity ρ for a system composed by a impurity inserted in a metal, described by a Fermi level resonance, utilizing a density of states obtained from X-ray Photoelectron Spectroscopy spectral density in the Kondo regime using the Anderson model obtained by Frota and Oliveira using the renormalization group technique in T = 0, in sequence generalized by Chattopadyay and Jarrel for T 6= 0, adjusting the results obtained by Quantum Monte Carlo technique, adding to the resonant level width Γ a factor γ(T) = 4.52T . Our results are in qualitative agreement with exact results obtained to Kondo model.
Keywords: Ressonância de Kondo; Kondo resonnance; CIÊNCIAS EXATAS E DA TERRA: FÍSICA